Legalisasi Produk Kopi Mangrove Melalui Pengurusan Izin Edar Pada UMKM Bale Mangrove - Alvian, Muhamad Riki; Tantri, Ni Luh Putu Diah; Ilmi, Amalia; Fahreza, Muhammad Naufal Rifa; Aidilla, Inggit Hawa; Afriani, Risca Nur; Arti, Meisya Auliya Nanda; Ismunandar, Adam; Yohana, Sri; Ramadhaniarsyah, Sekar Wahyu; Karyawan, I Dewa Made Alit (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Jerowaru Village, located in the Jerowaru subdistrict of East Lombok, West Nusa Tenggara, is known for its significant blue economy potential, particularly in the sectors of ecotourism and marine products. One of the village’s flagship products is mangrove coffee, a blend of robusta coffee beans and mangrove fruit from Dusun Poton Bako. Although mangrove coffee production began in November 2022, the product faces challenges related to legality and distribution permits, which limit its market reach. To address these issues, the 2024 Community Service Program (KKN PMD) University of Mataram aims to assist MSMEs Bale Mangrove in obtaining distribution permits by applying for a Business Identification Number (NIB) and a Household Industry Food Production Certificate (SPP-IRT). The method used involves supporting MSMEs in the legality process, including stages of planning, implementation of NIB and SPP-IRT creation, and evaluation to meet all licensing requirements. The results of this activity indicate that MSMEs understanding has improved, enabling them to handle the permit process effectively. In conclusion, the assistance provided by KKN PMD students in the licensing process contributes to the efficiency and legality of MSMEs, thereby enhancing the product’s competitiveness in a broader market and ensuring the business's sustainability in the future.